ThriveZA-Nurturing Sustainable Entrepreneurship for South African Youth: A Review - Sasi Gangiah (African Journal of Inter-Multidisciplinary Studies, 2024)
Recently, addressing entrepreneurship among South African youth has gained importance due to high unemployment rates and limited job prospects. Sustainable entrepreneurship offers a solution by generating employment, driving economic growth, and reducing poverty. This article outlines the current situation for South African youth, highlighting challenges and prospects related to entrepreneurship. It explores factors, strategies, and interventions that can foster a sustainable entrepreneurial spirit, emphasising the importance of an enabling environment through supportive policies and infrastructure. The article reviews recent literature on policies promoting sustainable entrepreneurship for South African youth, employing a semi-systematic content analysis approach. It focuses on improving the well-being of unemployed youth and the hurdles in educational institutions in fostering entrepreneurship. Preliminary findings emphasise the significance of funding access, business skills development, mentorship, and networking opportunities in nurturing sustainable entrepreneurship. The outcomes stress the need for comprehensive support mechanisms and policy actions to promote and sustain youth entrepreneurship. By cultivating an ecosystem conducive to entrepreneurial endeavours, South Africa can unlock the untapped entrepreneurial potential of its youth, fostering a more inclusive and prosperous future. Empowering young individuals to create job opportunities and contribute to the economy can yield significant benefits for individuals, communities, and society.